Pernikahan Dini Penduduk di Pulau Tidung – Kepulauan Seribu. Laporan Awal Pengabdian kepada Masyarakat FK UKI - Abraham Simatupang; Yunita Sitompul; Robert Sirait (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2023)
Although there are already restrictions on the age of marriage according to Law No. 16 of 2019 article 7 paragraph 1 which reads: Marriage is only allowed if the man and woman have reached the age of 19 (nineteen) years, early marriage is still a problem in Indonesia. Early marriage has quite a lot of impact not only on the marriage partner, but also on their descendants and families. The divorce rate is quite high and the health rate and family economy also have an effect. Based on this, in the FK UKI Community Service activities in June 2022, data collection has been carried out related to the early marriage history of residents of Tidung Island-Thousand Islands, Jakarta. There were 99 respondents who had a history of early marriage, with the youngest marriage age was 10 years old and the oldest was 18 years old. The last education they had graduated was elementary school (69.7%) with a job as “housewife